The impact of chromium ion stress on plant growth, developmental physiology, and molecular regulation - Saud, Shah; Wang, Depeng; Fahad, Shah; Javed, Talha; Jaremko, Mariusz; Abdelsalam, Nader R.; Ghareeb, Rehab Y. (Frontiers in Plant Science, 2022)
In recent years, heavy metals-induced soil pollution has increased due to the widespread usage of chromium (Cr) in chemical industries. The release of Cr into the environment has reached its peak causing hazardous environmental pollution. Heavy metal-induced soil pollution is one of the most important abiotic stress affecting the dynamic stages of plant growth and development. In severe cases, it can kill the plants and their derivatives and thereby pose a potential threat to human food safety. The chromium ion effect on plants varies and depends upon its severity range. It mainly impacts the numerous regular activities of the plant's life cycle, by hindering the germination of plant seeds, inhibiting the growth of hypocotyl and epicotyl parts of the plants, as well as damaging the chloroplast cell structures. In this review article, we tried to summarize the possible effects of chromium-induced stress on plant growth, developmental physiology, biochemistry, and molecular regulation and provided the important theoretical basis for selecting remedial plants in chromium-induced contaminated soils, breeding of low toxicity tolerant varieties, and analyzing the mechanism of plant resistance mechanisms in response to heavy metal stress.